Negative pole piece and application thereof

By reasonably matching graphite and amorphous crystalline silicon-based materials in the negative electrode sheet of lithium-ion batteries, the battery performance failure problem caused by volume expansion of silicon-based materials is solved, and a higher cycle life and energy density are achieved.

CN119852321AActive Publication Date: 2025-04-18ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411861507.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-18
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

In existing lithium-ion batteries, the volume expansion and contraction of silicon-based materials lead to failure of battery performance, especially during the cycle, problems such as material powdering, electrode damage and electrolyte drying seriously affect the service life of the battery.

Method used

By reasonably matching the first electrode sheet active material graphite and the second electrode sheet active material active material in the negative electrode sheet, the OI value of graphite and the crystallinity of the silicon material are controlled to meet specific relationships to reduce the volume expansion during lithium ions embedded and deintercalation.

Benefits of technology

It effectively reduces the volume expansion of the anode material during the lithium ion embedding and deintercalation process, improves the cycle life and energy density of the battery, and improves the conductivity and electrochemical performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure BDA0005193313340000051
    Figure BDA0005193313340000051
  • Figure BDA0005193313340000061
    Figure BDA0005193313340000061
Patent Text Reader

Abstract

The invention discloses a negative pole piece and application thereof, and belongs to the technical field of battery materials. The negative pole piece comprises a first pole piece active substance and a second pole piece active substance, the first pole piece active substance and the second pole piece active substance meet the following relation: 1 < = L * Xc / H < = 25; l represents the OI value of the first pole piece active substance, Xc represents the crystallinity of the second pole piece active substance, and H represents the thickness of the anode active substance. By setting the characteristic parameters of the first pole piece active substance and the second pole piece active substance to meet the specific relational expression, the problem of battery performance failure caused by silicon volume expansion is solved, and meanwhile, the battery conductivity and the energy density are also improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a negative electrode sheet and application thereof. Background Art

[0002] Lithium-ion batteries have outstanding advantages such as high energy density, no memory effect, long cycle life, fast charge and discharge, and low self-discharge, and are widely used in consumer electronics, electric vehicles, energy storage and other fields. As the market demand for the energy density and charging rate of lithium-ion batteries is getting higher and higher.

[0003] At present, the common method to improve energy density is to mix silicon-based materials into the negative electrode active material. However, during the charge and discharge process, lithium ions will be embedded in and out of the negative electrode active material mixed with silicon-based materials, causing the volume of the silicon-based materials to expand and contract. The serious volume change of silicon during the cycle leads to a series of consequences such as material pulverization, electrode damage and electrolyte drying up, and ultimately exhibits poor cycle performance. Due to the gradual increase in the mixing ratio of silicon negative electrode materials and the expansion problem of silicon, the thickness expansion rate of the battery cycle is large, which seriously affects the use of the entire machine.

[0004] Therefore, it is urgent to find an anode active material to solve the problem of silicon volume expansion leading to battery performance failure in the above-mentioned prior art. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a negative electrode plate, which solves the problem of battery performance failure caused by silicon volume expansion, and also improves the battery conductivity and energy density.

[0006] The present invention also provides a battery comprising the negative electrode plate.

[0007] According to an embodiment of the first aspect of the present invention, it is provided that the negative electrode plate includes a first electrode plate active material and a second electrode plate active material;

[0008] The first pole piece active material and the second pole piece active material satisfy the relationship: 1≤L*Xc / H≤25; L represents the OI value of the first pole piece active material, Xc represents the crystallinity of the second pole piece active material, and H represents the thickness of the anode active material.

[0009] The negative electrode sheet according to the embodiment of the present invention has at least the following beneficial effects:

[0010] The negative electrode plate of the present invention includes a first electrode plate active material and a second electrode plate active material. The characteristic parameters of the first electrode plate active material graphite and the second electrode plate active material amorphous crystalline silicon-based material (such as the OI value of graphite and the crystallinity of silicon material) are set to meet a specific relationship, thereby effectively reducing the volume expansion of the anode material during the lithium ion insertion and deinsertion process, especially the expansion in the thickness direction. By controlling the OI value of graphite, the lattice expansion in the XYZ axis direction is dispersed, the performance degradation of the battery caused by expansion is reduced, and the cycle life of the battery is improved. If the graphite OI value is small, the expansion generated during the cyclic charge and discharge process is smaller. This is because the lithium ions will be embedded in the graphite interlayer spacing during the lithium insertion process, so that the interlayer spacing expands, causing the graphite to expand; while the isotropic graphite material undergoes lattice expansion in multiple directions, thereby dispersing the expansion of the battery in the thickness direction. When the OI value is within the range specified by the present invention and satisfies the relationship, the expansion difference of the negative electrode active layer is relatively moderate, which can improve the electrolyte infiltration of the negative electrode, reduce the expansion of the battery core, and improve the battery performance.

[0011] The present invention adjusts the crystallinity of the second pole piece active material to control it to have a certain electronic conductivity while maintaining good volume change stability. The critical rupture size of the lithiation reaction of the second pole piece active material is large, which can effectively deal with the problem of volume expansion of silicon materials during charging and discharging, while maintaining moderate conductivity, balancing the electronic conduction and lithium ion diffusion characteristics, and improving the overall electrochemical performance of the battery. The silicon atoms in crystalline silicon are arranged in a long-range order, and the diffusion path and interphase deformation of lithium are highly anisotropic; while the silicon atoms in amorphous silicon are arranged in a long-range disorder, and the critical rupture size of the lithiation reaction is much larger than that of crystalline silicon. The isotropy of amorphous silicon helps to solve the volume change problem of lithium alloying, but this long-range disordered structure makes the electronic conductivity of amorphous silicon much lower than that of crystalline silicon. Lithium battery materials need to have both electronic and lithium ion conduction characteristics. Therefore, the present invention balances this relationship by regulating amorphous crystalline silicon particles with a certain degree of crystallinity, and has moderate electronic conductivity and isotropic characteristics.

[0012] The present invention limits the OI value of the first pole piece active material graphite and the crystallinity of the second pole piece active material silicon-based material to work synergistically within a limited range, the pore structure of the pole piece is optimized, the electrolyte can better penetrate into the negative electrode active material layer, the wettability of the electrode is improved, thereby improving the charge and discharge efficiency of the battery and reducing the increase in resistance caused by the accumulation of electrolyte on the pole piece surface.

[0013] Wherein, OI=I(004) / I(110), I(004) is the integrated area of ​​the diffraction peak of the (004) crystal plane, and I(110) is the integrated area of ​​the diffraction peak of the (110) crystal plane;

[0014] Xc=Ic / (Ic+Ia), Ic is the integrated diffraction intensity of the crystalline part, and Ia is the integrated scattering intensity of the amorphous part.

[0015] According to some embodiments of the present invention, the first pole piece active material is graphite.

[0016] According to some embodiments of the present invention, the graphite includes at least one of artificial graphite and natural graphite.

[0017] According to some embodiments of the present invention, the second pole piece active material is an amorphous crystalline silicon-based material.

[0018] According to some embodiments of the present invention, the amorphous crystalline silicon-based material includes at least one of silicon, silicon carbon, silicon oxygen and silicon alloy.

[0019] According to some embodiments of the present invention, L is 2 to 12, for example, it can be 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, or 12.

[0020] According to some embodiments of the present invention, the Xc is 20.6% to 62.8%.

[0021] Preferably, the Xc is 29.8% to 62.8%.

[0022] According to some embodiments of the present invention, H is 25-70 μm.

[0023] Preferably, H is 35-50 μm.

[0024] According to some embodiments of the present invention, the particle size D50 of the first pole piece active material is 11-17 μm.

[0025] Preferably, the particle size D50 of the first pole piece active material is 15-17 μm.

[0026] According to some embodiments of the present invention, the particle size D50 of the second pole piece active material is 5.5-11 μm.

[0027] Preferably, the particle size D50 of the second pole piece active material is 8-10 μm.

[0028] According to some embodiments of the present invention, the difference in particle size D50 between the first pole piece active material and the second pole piece active material is 2-8 μm, and the particle size of the first pole piece active material is larger than that of the second pole piece active material.

[0029] When used in combination, the second electrode active material can effectively fill the gaps in the first electrode active material, thereby increasing the compaction density of the negative electrode, which not only increases the volume energy density of the electrode, but also reduces the compaction rebound of the electrode, thereby increasing the energy output of the battery. If the graphite particle size is smaller than that of the silicon particle, the graphite particles are embedded between the silicon particles, which cannot effectively limit the lithium expansion of the silicon particles. At the same time, the compaction density of small-diameter graphite is low, which is not conducive to the energy density of the battery.

[0030] According to some embodiments of the present invention, the anode active material includes, in terms of mass percentage: 70% to 97% of the first pole piece active material; and 3% to 30% of the second pole piece active material.

[0031] According to some embodiments of the present invention, the mass ratio of the first pole piece active material to the second pole piece active material is 9:1 to 7:3; for example, it may be 9:1, 8:2, or 7:3.

[0032] According to some embodiments of the present invention, the grain size of the second pole piece active material is 10-17 nm.

[0033] The grain size of the present invention affects the charge and discharge performance. The smaller the grain, the shorter the lithium ion embedding channel, which is more conducive to the alloying of silicon and lithium, so that it can quickly reach a fully embedded lithium state, thereby having better charge and discharge performance; the grain size also affects the cycle performance. Small-sized grains can show better electrochemical performance, slow down the volume expansion and contraction of silicon particles when lithium is embedded and released, avoid material crack expansion and material pulverization, and affect the cycle life.

[0034] According to some embodiments of the present invention, the half-peak width of the XRD (111) crystal plane diffraction peak of the second pole piece active material is 0.4 to 0.75.

[0035] The half-peak width of the crystal plane diffraction peak is mainly related to the crystallinity of the material. The smaller the half-peak width, the higher the crystallinity.

[0036] According to some embodiments of the present invention, the negative electrode plate further comprises a current collector disposed between the first electrode plate active material and the second electrode plate active material.

[0037] According to an embodiment of the second aspect of the present invention, there is provided a lithium-ion battery comprising the above-mentioned negative electrode plate.

[0038] If there is no special explanation, the actual meaning of “about” in the present invention is that the error is allowed to be within the range of ±2%, for example, about 100 is actually 100±2%×100.

[0039] Other features and advantages of the present invention will be set forth in the description which follows, and in part will be apparent from the description, or may be learned by practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0041] Figure 1 This is a diagram of the structure of the active material of the electrode in Example 1 of the present invention. DETAILED DESCRIPTION

[0042] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0043] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.

[0044] In the description of the present invention, unless otherwise clearly defined, terms such as setting, installing, connecting, etc. should be understood in a broad sense, and technicians in the relevant technical field can reasonably determine the specific meanings of the above terms in the present invention based on the specific content of the technical solution.

[0045] In the description of the present invention, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0046] In the present invention, in order to achieve a specific crystallinity of the amorphous crystalline silicon-based material of the second electrode active material and an OI value of the first anode active material, the following preparation and control methods are adopted:

[0047] In the specific implementation, the preparation method of silicon-based materials is not strictly limited, and a variety of methods well known to those skilled in the art can be used to obtain silicon-based materials, including but not limited to chemical vapor deposition, mechanical alloying, solution method, high-temperature pyrolysis, and mechanical ball milling. The following is a specific preparation and regulation example:

[0048] The polyphenolic resin was dissolved in acetone in a ratio of 50:50, and an aqueous solution of phosphoric acid with a mass fraction of 85% was added to the solution and shaken. The above reaction solution was placed at 55°C for 12h, then cured at 120°C for 6h, and then pyrolyzed and carbonized at 800°C under nitrogen protection. The carbonized carbon matrix was heated to 800°C at 150°C / h under nitrogen protection, and water vapor (0.3-5mL / min) was introduced for activation reaction, and the activation time was 80-100min. The particle size was adjusted with a crusher according to the target size of the material to obtain a carbon matrix with a certain particle size. The carbon matrix was placed in a tubular furnace, silane gas was introduced, nitrogen was used as a carrier gas and diluent gas, and the gas-generating silicon base was decomposed at 400-800°C, and then a silicon-based material was obtained. Silicon-based materials with different crystallinity can be obtained by adjusting the decomposition temperature.

[0049] In specific implementation, the OI value of graphite has been regulated during the secondary particle coating stage at the supplier end.

[0050] Example 1

[0051] This embodiment provides a negative electrode plate, and the characteristics of the active material of the plate are as follows:

[0052] L represents the OI value of the first electrode active material is 2; Xc represents the crystallinity of the second electrode active material is 29.8, and H represents the thickness of the anode active material is 35 μm; L*Xc / H=1.70;

[0053] The first pole piece active material is graphite, with a particle size D50 of 15 μm, and the second pole piece active material is silicon, with a particle size D50 of 8 μm; the results of the pole piece active material are as follows Figure 1 shown.

[0054] This embodiment also provides a method for preparing the above-mentioned negative electrode sheet: the sheet active material, conductive agent (SP and CNT mixed in a mass ratio of 0.45:0.05), and binder (SBR and PAALi mixed in a mass ratio of 0.5:1.8) are mixed in a weight ratio of 97.7:1.1:1.2 to obtain an anode active material slurry, which is evenly coated on the surfaces of both sides of the negative electrode collector, and then cold pressed and stripped to obtain a negative electrode sheet.

[0055] This embodiment also provides a lithium ion battery, and the specific preparation method includes:

[0056] Positive electrode sheet: The cathode active material LiCoO2, the conductive agent acetylene black, the conductive carbon nanotubes, and the binder polyvinylidene fluoride (PVDF) are fully dispersed in an N-methylpyrrolidone solvent system in a weight ratio of 97.6:0.5:0.6:1.3 and evenly coated on the surfaces of both sides of the positive electrode current collector.

[0057] Isolation film: The PE surface is coated with a ceramic mixture as an isolation film.

[0058] Electrolyte: Ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and propyl propionate (PP) are mixed in a volume ratio of 1.2:1:4:4, and then fully dried lithium salt LiPF6 is dissolved in a mixed organic solvent at a ratio of 1 mol / L to prepare an electrolyte.

[0059] Preparation of a full battery: The positive electrode sheet, separator, and negative electrode sheet are wound or stacked to produce a bare cell, which is then packaged and injected with electrolyte to produce a finished lithium-ion battery.

[0060] The characteristics of the electrode active materials of Examples 2 to 8 and Comparative Examples 1 to 4 are shown in Table 1, and the rest are the same as Example 1.

[0061] Table 1 Characteristics of active materials in the electrode sheets of Examples 2 to 8 and Comparative Examples 1 to 4

[0062]

[0063]

[0064] Performance Testing:

[0065] Compacted density:

[0066] The electrode sheet is placed in a rolling device, and the electrode sheet thickness is adjusted by adjusting the rolling pressure. The compaction density is β, the mass of the negative electrode active material is M, the force area of ​​the negative electrode active material is S, the thickness of the electrode sheet sample after rolling is H, and the compaction density calculation formula is as follows: β = M / (S×H).

[0067] Cycle test method:

[0068] In an environment of 25℃, the cycle test was carried out according to the following method. Charging mode: 2.8C CC to 4.25V, 2C CC to4.35V, CV to 1.8C, 1.8C CC to 4.4V, CV to 1.5C, 1.5C CC to 4.5V, CV to 1.2C, 1.2CCC to 4.55V, CV to0.26C; Discharging mode: 0.7C DC to 3.0V.

[0069] Among them, Fading is the capacity retention rate, Swelling is the thickness expansion rate; the calculation formula is as follows:

[0070] 500-week Fading = discharge capacity of the 500th week / discharge capacity of the 1st week * 100%;

[0071] 500-week Swelling = discharge thickness of the 500th week / discharge thickness of the 1st week * 100%;

[0072] DCR test:

[0073] The battery was charged to 4.5V at 0.5C, with a cut-off current of 0.02C and left for 5 minutes; it was discharged at a current of 1A for 500ms.

[0074] DCR = (voltage before discharge - voltage after discharge) / current;

[0075] The performance test results of the embodiments of the present invention and the comparative examples are shown in Table 2.

[0076] Table 2 Performance test results of embodiments and comparative examples

[0077]

[0078]

[0079] It can be seen from Table 2 that the lithium-ion battery of the embodiment of the present invention shows good performance capacity retention rate (Fading) and battery expansion rate (Swelling) in the 500-week cycle test. For example, the 500-week Swelling of Example 10 is 7.77%, and the Fading is 89.34%. Compared with the poor performance in the comparative example (such as the Swelling of Comparative Example 7 is 20.57%, and the Fading is 72.55%), it shows that the active material combination of the present invention can effectively inhibit the capacity decay and expansion of the battery. While improving the cycle performance, the present invention maintains good resistance characteristics. The DCR test results in the embodiment are relatively low, indicating that on the basis of the optimized design of the negative electrode material, the internal resistance can be effectively reduced to ensure the performance stability of the battery under high power conditions. By regulating the particle size of the material and the thickness of the coating, the compaction density of the present invention is between 1.6 and 1.72 g / cm 3 Compared with the comparative example, a higher energy density can be achieved, which shows that the present invention not only optimizes the cycle stability, but also improves the energy storage capacity of the battery. The present invention shows through experiments that the parameter relationship of L*Xc / H of the anode active material has a significant impact on the final battery performance. The reasonable L*Xc / H ratio in the embodiment (such as 3.53 in Example 7 and 7.15 in Example 10) brings better electrochemical performance.

[0080] It can be seen that the anode active material of the present invention can significantly improve the cycle performance of lithium-ion batteries in the negative electrode sheet, solve the problem of battery failure caused by expansion and deformation of the negative electrode sheet, and at the same time the battery cell also has good conductivity and good energy density.

[0081] The embodiments of the present invention are described in detail above in conjunction with the accompanying drawings, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present invention. In addition, the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

Claims

1. A negative electrode plate, characterized in that: The negative electrode plate includes a first plate active material and a second plate active material; The first pole piece active material and the second pole piece active material satisfy the relationship: 1≤L*Xc / H≤25; L represents the OI value of the first pole piece active material, Xc represents the crystallinity of the second pole piece active material, and H represents the thickness of the anode active material.

2. The anode active material according to claim 1, characterized in that: The first pole piece active material is graphite; preferably, the second pole piece active material is an amorphous crystalline silicon-based material; preferably, the amorphous crystalline silicon-based material includes at least one of silicon, silicon carbon, silicon oxygen and silicon alloy.

3. The negative electrode sheet according to claim 1, characterized in that: The L is 2-12.

4. The negative electrode sheet according to claim 1, characterized in that: The Xc is 20.6% to 62.8%.

5. The negative electrode sheet according to claim 1, characterized in that: The H is 25 to 70 μm.

6. The negative electrode sheet according to claim 1, characterized in that: The particle size D50 of the first pole piece active material is 11 to 17 μm; preferably, the particle size D50 of the second pole piece active material is 5.5 to 11 μm; preferably, the difference in particle size D50 between the first pole piece active material and the second pole piece active material is 2 to 8 μm, and the particle size of the first pole piece active material is larger than that of the second pole piece active material.

7. The negative electrode sheet according to claim 1, characterized in that: In terms of mass percentage, the anode active material includes: 70% to 97% of the first pole piece active material and 3% to 30% of the second pole piece active material.

8. The negative electrode sheet according to claim 1 or 2, characterized in that: The grain size of the second pole piece active material is 10-17 nm.

9. The negative electrode sheet according to claim 1, characterized in that: The negative electrode plate further includes a current collector disposed between the first electrode plate active material and the second electrode plate active material.

10. A lithium ion battery, characterized in that: Comprising the negative electrode sheet as described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Negative electrode plate with silicon-carbon composite structure and battery comprising negative electrode plate

    CN114005958A

  • Negative pole piece, preparation method thereof and lithium secondary battery

    CN114759157A

  • Lithium ion secondary battery

    CN116613302A

  • Negative pole piece, secondary battery, battery pack, battery module and electric device

    CN116636050A

  • Negative plate, preparation method thereof and lithium ion battery

    CN117117080A